2015
DOI: 10.1007/s13258-015-0294-1
|View full text |Cite
|
Sign up to set email alerts
|

Molecular genetics-nutrition interactions in the expression of AANAT, ADRB3, BTG2 and FASN genes in the heart, kidney and liver of Australian lambs supplemented with Spirulina (Arthrospira platensis)

Abstract: Quantitative reverse transcriptase polymerase chain reaction was used to assess the messenger RNA (mRNA) transcription levels and expressions of Aralkylamine N-acetyltransferase, Adrenergic beta-3 receptor, B cell translocation gene 2, and Fatty acid synthase genes. In total, 432 heart, kidney and liver samples from 48 purebred and crossbred Australian prime lambs supplemented with Spirulina (Arthrospira platensis) blue-green cyanobacterial microalgae over a 9-week feeding trial were utilized for fatty acid co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 35 publications
2
6
0
Order By: Relevance
“…Other previous studies had demonstrated that the nutritional background of pasture-fed ruminants confers a higher muscle α-tocopherol antioxidant status compared to those on concentrate based diets [ 60 , 61 , 62 , 63 , 64 ]. Several internal and external factors influence the quantity and quality of lipids in animal products due to genetics-nutrition interactions in the expression of genes controlling fat metabolism [ 65 ] and these include the key attributes of fat melting point, intramuscular fat and fatty acid composition. The Folin–Ciocalteu total phenolics, ferric reducing antioxidant power and antioxidant enzyme activities of glutathione peroxidase, catalase and superoxide dismutase values in the present study were consistent with those reported in the Longissimus thoracis et lumborum muscle [ 26 ], liver and plasma [ 27 ] of lambs grazing ryegrass.…”
Section: Discussionmentioning
confidence: 99%
“…Other previous studies had demonstrated that the nutritional background of pasture-fed ruminants confers a higher muscle α-tocopherol antioxidant status compared to those on concentrate based diets [ 60 , 61 , 62 , 63 , 64 ]. Several internal and external factors influence the quantity and quality of lipids in animal products due to genetics-nutrition interactions in the expression of genes controlling fat metabolism [ 65 ] and these include the key attributes of fat melting point, intramuscular fat and fatty acid composition. The Folin–Ciocalteu total phenolics, ferric reducing antioxidant power and antioxidant enzyme activities of glutathione peroxidase, catalase and superoxide dismutase values in the present study were consistent with those reported in the Longissimus thoracis et lumborum muscle [ 26 ], liver and plasma [ 27 ] of lambs grazing ryegrass.…”
Section: Discussionmentioning
confidence: 99%
“…The proteins of the FABP4 family are small molecular-weight proteins that have a high binding affinity for long-chain fatty acids, participate in fatty-acid transportation from the plasma membrane to the sites of β-oxidation, triacylglycerol, and phospholipid synthesis, and variation in FABP4 gene has been reported to affect fat deposition, growth, and meat production in sheep [71,72]. Several other research findings in sheep have demonstrated that dietary manipulation of omega-3 fatty acids can influence intramuscular fat deposition, growth, milk, wool, and meat quality [42,[73][74][75][76][77][78][79][80][81][82][83][84][85][86][87][88][89][90], while only a handful of studies [52,[91][92][93] have validated independent associations of carcass quality, shear force, intramuscular fat percentage, and omega-3 polyunsaturated fatty acid content with gene markers or the expression of genes encoding enzymes regulating fat metabolism in Australian lamb. Therefore, our current findings at the FABP4 g.62829478A>-SNP locus showing consistently positive correlations between IMF and n-3 LC-PUFA of up to 0.66 with DHA, 0.47 with DPA, and 0.38 with EPA (Figure 9 and Tables 5 and 6) provides a novel molecular marker for TAW sheep producers to select and breed lambs that are not only of high meat-eating quality, but also provide a healthy product for brain growth and development.…”
Section: Fabp Gene Polymorphismmentioning
confidence: 99%
“…Moderate heritabilities for the whole group of n-3 PUFA were reported by Boichard et al [151] and Maroteau et al [152], and could be explained by major contribution of the shorter chain n-3 PUFA. First identified in the human genome in 2000 [153], fatty acid desaturase 1 and 2 (FADS1 and FADS2) are considered as the major candidate genes that regulate the endogenous synthesis of n-3 LC-PUFA from ALA in mammals including ruminants [154,155,156,157,158]. The first effort to define the association between these two encoding genes and n-3 PUFA in the milk of Holstein cows [159] found that three significant single nucleotide polymorphism (SNP) markers within FADS1 and FADS2 were associated with EPA.…”
Section: Recent Attempts To Increase N-3 Pufa Content In Dairy-dermentioning
confidence: 99%